Eosinophils, Hypoxia-Inducible Factors, and Barrier Dysfunction in Functional Dyspepsia - Hari, Suraj; Burns, Grace L.; Hoedt, Emily C.; Keely, Simon; Talley, Nicholas J. (Frontiers in Allergy, 2022)
Functional dyspepsia (FD) is a highly prevalent disorder of gut-brain interaction (DGBI), previously known as a functional gastrointestinal disorder. Characterized by early satiety, postprandial fullness, and/or epigastric pain or burning, diagnosis depends on positive symptomatology and exclusion of obvious structural diseases. A subtle inflammatory phenotype has been identified in FD patients, involving an increase in duodenal mucosal eosinophils, and imbalances in the duodenal gut microbiota. A dysregulated epithelial barrier has also been well described in FD and is thought to be a contributing factor to the low-grade duodenal inflammation observed, however the mechanisms underpinning this are poorly understood. One possible explanation is that alterations in the microbiota and increased immune cells can result in the activation of cellular stress response pathways to perpetuate epithelial barrier dysregulation. One such cellular response pathway involves the stabilization of hypoxia-inducible factors (HIF). HIF, a transcriptional protein involved in the cellular recognition and adaptation to hypoxia, has been identified as a critical component of various pathologies, from cancer to inflammatory bowel disease (IBD). While the contribution of HIF to subtle inflammation, such as that seen in FD, is unknown, HIF has been shown to have roles in regulating the inflammatory response, particularly the recruitment of eosinophils, as well as maintaining epithelial barrier structure and function. As such, we aim to review our present understanding of the involvement of eosinophils, barrier dysfunction, and the changes to the gut microbiota including the potential pathways and mechanisms of HIF in FD. A combination of PubMed searches using the Mesh terms functional dyspepsia, functional gastrointestinal disorders, disorders of gut-brain interaction, duodenal eosinophilia, barrier dysfunction, gut microbiota, gut dysbiosis, low-grade duodenal inflammation, hypoxia-inducible factors (or HIF), and/or intestinal inflammation were undertaken in the writing of this narrative review to ensure relevant literature was included. Given the findings from various sources of literature, we propose a novel hypothesis involving a potential role for HIF in the pathophysiological mechanisms underlying FD.